Analisis Penggunaan Bahasa Indonesia pada Kemasan Produk Makanan dan Minuman Ringan - Iqbal, Naufaldy; Fitriani, Sella Olivia; Halim, Christina; Ababil, Zulfaz Refie; Nurhayati, Eni (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
Indonesian is a language that is a unit in the State of Indonesia which is a tool to be able to communicate between people. The purpose of this study is to analyze how errors - both in terms of spelling and from the structure of phrases - are used on food and soft drink product packaging. This study used a descriptive method, namely research conducted by observing something (object of research) and then explaining what was observed. The results of this study indicate that there are still errors in the use of some food and soft drink products. These errors include spelling and inaccuracies in phrase structure. The result of this research is the discovery of several food and soft drink products that still have deviations such as losing phonemes, adding phonemes, and changing phonemes. Deviations at the phonological level on the packaging of food and soft drink products are the main attraction and give a unique impression to consumers.